Size Distribution of Sperm Whales Acoustically Identified during Long Term Deep-Sea Monitoring in the Ionian Sea - Caruso, Francesco; Sciacca, Virginia; Bellia, Giorgio; De Domenico, Emilio; Larosa, Giuseppina; Papale, Elena; Pellegrino, Carmelo; Pulvirenti, Sara; Riccobene, Giorgio; Simeone, Francesco; Speziale, Fabrizio; Viola, Salvatore; et al. (PLOS ONE, 2015)
The sperm whale (Physeter macrocephalus) emits a typical short acoustic signal, defined as a “click”, almost continuously while diving. It is produced in different time patterns to acoustically explore the environment and communicate with conspecifics. Each emitted click has a multi-pulse structure, resulting from the production of the sound within the sperm whale’s head. A Stable Inter Pulse Interval (Stable IPI) can be identified among the pulses that compose a single click. Applying specific algorithms, the measurement of this interval provides useful information to assess the total length of the animal recorded. In January 2005, a cabled hydrophone array was deployed at a depth of 2,100 m in the Central Mediterranean Sea, 25 km offshore Catania (Ionian Sea). The acoustic antenna, named OνDE (Ocean noise Detection Experiment), was in operation until November 2006. OνDE provided real time acoustic data used to perform Passive Acoustic Monitoring (PAM) of cetacean sound emissions. In this work, an innovative approach was applied to automatically measure the Stable IPI of the clicks, performing a cepstrum analysis to the energy (square amplitude) of the signals. About 2,100 five-minute recordings were processed to study the size distribution of the sperm whales detected during the OνDE long term deep-sea acoustic monitoring. Stable IPIs were measured in the range between 2.1 ms and 6.4 ms. The equations of Gordon (1991) and of Growcott (2011) were used to convert the IPIs into measures of size. The results revealed that the sperm whales recorded were distributed in length from about 7.5 m to 14 m. The size category most represented was from 9 m to 12 m (adult females or juvenile males) and specimens longer than 14 m (old males) seemed to be absent.